2021
DOI: 10.1177/03635465211044458
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of New Knee Injuries in Female Soccer Players After Primary Anterior Cruciate Ligament Reconstruction at 5- to 10-Year Follow-up

Abstract: Background: A new anterior cruciate ligament (ACL) injury after ACL reconstruction is a feared outcome. Purpose: To study the risk of new knee injuries in female soccer players 5 to 10 years after primary unilateral ACL reconstruction and to compare players who returned to soccer with (1) players who did not return and (2) knee-healthy soccer players (controls). Study Design: Cohort study; Level of evidence, 2. Methods: Demographic, soccer-specific, and surgical data were recorded at baseline for 317 female so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
(64 reference statements)
0
29
2
1
Order By: Relevance
“…However, rerupture rates up to 27% were found after ACL reconstruction in younger athletes and with longer follow-up periods. 4 , 11 , 12 , 26 , 44 In the present study, the rate of recurrent instability at 5 years after ACL reconstruction with a hamstring tendon autograft was 20% and was not significantly more favorable in comparison with ACL repair with DIS. Although the rate of recurrent instability after ACL reconstruction in the present study was higher than in reports of graft failure after ACL reconstruction with a hamstring tendon graft in comparable age groups (up to 8% 40 , 42 , 45 ), it was within the range of graft failure rates (up to 28.3%) in a recent systematic review of comparative studies by Belk et al, 5 who revealed inconsistency in clinical outcomes at midterm follow-up after ACL reconstruction with hamstring tendon autografts.…”
Section: Discussioncontrasting
confidence: 44%
“…However, rerupture rates up to 27% were found after ACL reconstruction in younger athletes and with longer follow-up periods. 4 , 11 , 12 , 26 , 44 In the present study, the rate of recurrent instability at 5 years after ACL reconstruction with a hamstring tendon autograft was 20% and was not significantly more favorable in comparison with ACL repair with DIS. Although the rate of recurrent instability after ACL reconstruction in the present study was higher than in reports of graft failure after ACL reconstruction with a hamstring tendon graft in comparable age groups (up to 8% 40 , 42 , 45 ), it was within the range of graft failure rates (up to 28.3%) in a recent systematic review of comparative studies by Belk et al, 5 who revealed inconsistency in clinical outcomes at midterm follow-up after ACL reconstruction with hamstring tendon autografts.…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, Guy et al 20 recently found that 37.3% of elite skiers experienced contralateral ruptures. Furthermore, a recent study by Fältström et al 11 identified female soccer players from the Swedish National Knee Ligament Registry and found a 17.8% rate of contralateral ACL injuries. Players who returned to soccer had a 5 times higher risk of contralateral ACL injury than players who did not return.…”
Section: Discussionmentioning
confidence: 99%
“…63 After ACLR, second ACL injuries occur in 14% to 22% of patients over the first 5 years, 9,27,31,39,47,56,60,62 and a recent study of female Swedish soccer players reported repeat ACL injury rates as high as 42% in those who returned to soccer, at a mean of 6.5 years. 15…”
mentioning
confidence: 99%